2016
DOI: 10.1097/igc.0000000000000804
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Risk of Ovarian Malignancy Algorithm Against CA125 and HE4 in Connection With Ovarian Cancer

Abstract: The results presented support the use of ROMA to improve clinical decision making, most notably in patients with early OC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 29 publications
1
45
0
1
Order By: Relevance
“…29 CA-125 as a standalone screening test is relatively insensitive for ovarian cancer, finding only about 60% of women with ovarian cancer. 30 Other serum biomarkers such as human epididymis protein (HE4) and human chorionic gonadotropin (HCG) have been tested in combination with CA-125 to improve performance characteristics of serum biomarker screening for ovarian cancer as standalone serum screening tests, 29,31 though evidence suggests that CA-125 is the most robust biomarker of the group. 32 …”
Section: When It Is Not So Simple To Screen: Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…29 CA-125 as a standalone screening test is relatively insensitive for ovarian cancer, finding only about 60% of women with ovarian cancer. 30 Other serum biomarkers such as human epididymis protein (HE4) and human chorionic gonadotropin (HCG) have been tested in combination with CA-125 to improve performance characteristics of serum biomarker screening for ovarian cancer as standalone serum screening tests, 29,31 though evidence suggests that CA-125 is the most robust biomarker of the group. 32 …”
Section: When It Is Not So Simple To Screen: Ovarian Cancermentioning
confidence: 99%
“…26,33 The UK trial tested a proprietary algorithm named ROCA ® that adjusted the biomarker level cut-off for normal results based on women’s clinical characteristics and the TV ultrasound result. 31 The promotion of ROCA ® (Abcodia, Cambridgeshire, UK) serum testing with TV ultrasound ran afoul of the Food and Drug Administration (FDA) for the claim that the ROCA ® test detects ovarian cancer early and reduced mortality. In late 2016 FDA issued a warning against using commercial screening tests for ovarian cancer, saying that, especially for women at high risk for hereditary ovarian cancer, “women and their doctors may not take appropriate actions to reduce their future risk if they rely on a result that shows no cancer currently present.” 34 FDA further stipulated that they did not recommend the use of ovarian cancer screening tests in the general population.…”
Section: When It Is Not So Simple To Screen: Ovarian Cancermentioning
confidence: 99%
“…For instance, in September 2011, the FDA approved human epididymis protein 4 (HE4) as a biomarker for monitoring patients with epithelial OVCA . A “Risk of Ovarian Malignancy Algorithm” (ROMA) utilizing combined serum measurements of HE4 and CA125 demonstrated increased sensitivity in diagnosing OVCA, particularly in the early‐stage patient group . The Tainsky laboratory has also defined specific paraneoplastic autoantibodies as potential markers for initial diagnosis and recurrent disease …”
Section: Discussionmentioning
confidence: 99%
“…However, CA-125 detection is poorly performed in the diagnosis of patients with early ovarian cancer [5]. The study has reported that the sensitivity and speci city of CA125 are 0.796 and 0.825 [6]. Although HE4 has greater speci city than CA125, the sensitivity has a varying result [6][7][8].…”
Section: Introductionmentioning
confidence: 99%